2015
DOI: 10.4055/cios.2015.7.3.298
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Incidence of Deep Vein Thrombosis after Hip Fractures in Korean

Abstract: BackgroundThe purpose of the current study was to investigate the incidence of preoperative deep vein thrombosis (DVT) after hip fractures in Korea.MethodsIn this prospective study, we enrolled 152 Korean geriatric patients who had suffered hip fractures due to a simple fall and were hospitalized between January 2013 and December 2013. There were 52 male and 100 female patients, and their mean age was 78.2 years. There were 96 trochanteric fractures and 56 femoral neck fractures. All patients were examined for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 20 publications
(22 reference statements)
2
53
4
1
Order By: Relevance
“…Recent studies have demonstrated that a significant proportion of the patients with hip fracture (HF) already had DVT preoperatively, and stressed out the importance of DVT diagnosis by using preoperative screening with doppler USG or venography [ 5 – 7 , 9 , 10 ]. However, preoperative DVT screening in all HF patients with a gold standard contrast venography might not be appropriate because of its invasiveness (such as pain, contrast medium reaction, and contrast-induced renal toxicity), and lack of venous access in some elderly HF patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have demonstrated that a significant proportion of the patients with hip fracture (HF) already had DVT preoperatively, and stressed out the importance of DVT diagnosis by using preoperative screening with doppler USG or venography [ 5 – 7 , 9 , 10 ]. However, preoperative DVT screening in all HF patients with a gold standard contrast venography might not be appropriate because of its invasiveness (such as pain, contrast medium reaction, and contrast-induced renal toxicity), and lack of venous access in some elderly HF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding to the incidence of acute preoperative DVT, our finding was comparable with the previous studies [ 6 – 10 ]. However, one previous study had demonstrated the incidence was only as 1.4% among the HF patients who were admitted within 72 h after injury, while increased as 13.3% among those who were admitted later than 72 h after injury [ 5 ]. These findings implied that the time delay from HF injury to admission and receiving the surgical treatment should be a significant predictive factor for the development of acute preoperative DVT [ 4 , 5 ], and might be one responsible cause for the variation of the incidence of acute preoperative DVT among the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Owing to trauma itself, immobilization, advanced age, and comorbidity, some patients experience perioperative complications. Deep vein thrombosis (DVT) of the lower extremities is one of the common complications in these patients, 2 which is a high risk of fatal pulmonary embolism in some patients. 3 Traditionally, chemical 4 and mechanical thromboprophylaxes 5 are well-established routines in the prevent and treatment of DVT.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the results of Adam and Zhang [12,13] , the incidence of hip fracture (74.90%) was relatively high. Considering that the three risk factors of Virchow were mostly present in the patients with hip fracture [14] .We should pay attention to the screening of DVT in these patients with fractures at speci c sites, and formulate reasonable individualized prevention and treatment strategies.Meizoso et al used RAP score in a retrospective cohort study of 1233 trauma patients and found that transfusion of more than 4 units was an independent risk factor for DVT [15] .The preoperative, intraoperative and postoperative blood transfusion rates of 569 patients in this study were 8.44% (48/569), 29.70% (169/569), and 13.88% (79/569), respectively.It was further found that intraoperative blood transfusion and postoperative blood transfusion were independent risk factors for postoperative DVT, while preoperative blood transfusion was not correlated with DVT.Perhaps we should reconsider the indications and necessity of blood transfusion in practice.Song et al reported that most patients with postoperative DVT had complicated DVT before surgery [16] ,In this study, preoperative DVT occurred in 26.71% of the patients, which was considered to be related to the longer average preoperative waiting time.Most of the current recommendations are that surgery should be performed as soon as possible within 48 hours after trauma to reduce the incidence of VTE [17] .But in practice, 66 percent of patients with hip fractures delayed surgery [18] .The reasons for delayed surgery may be as follows. 67.66% (385/569) of the patients were transferred to our hospital from other hospitals due to serious illness or limited medical conditions.Preoperative preparation for patients with medical diseases and routine preoperative examinations such as DVT screening will also delay surgery.Recently, Luksameearunothai et al con rmed that Caprini score ≥ 12 points should be used for preoperative ultrasound examination in elderly patients with hip fracture and patients with Wells score ≤ 1 points can be safely operated immediately [19] .There is a con ict between adequate preoperative preparation and early surgery and how to achieve a comprehensive and scienti c evaluation of severe patients is the key to avoid unnecessary delay in surgery.…”
Section: Discussionmentioning
confidence: 99%